Nuclear γ-tubulin associates with nucleoli and interacts with tumor suppressor protein C53 - Hořejší, Barbora; Vinopal, Stanislav; Sládková, Vladimíra; Dráberová, Eduarda; Sulimenko, Vadym; Sulimenko, Tetyana; Vosecká, Věra; Philimonenko, Anatoly; Hozák, Pavel; Katsetos, Christos D; Dráber, Pavel (Journal of cellular physiology, 2012)
γ-Tubulin is assumed to be a typical cytosolic protein necessary for nucleation of microtubules from microtubule organizing centers. Using immunolocalization and cell fractionation techniques in combination with siRNAi and expression of FLAG-tagged constructs, we have obtained evidence that γ-tubulin is also present in nucleoli of mammalian interphase cells of diverse cellular origins. Immunoelectron microscopy has revealed γ-tubulin localization outside fibrillar centers where transcription of ribosomal DNA takes place. γ-Tubulin was associated with nucleolar remnants after nuclear envelope breakdown and could be translocated to nucleoli during mitosis. Pretreatment of cells with leptomycin B did not affect the distribution of nuclear γ-tubulin, making it unlikely that rapid active transport via nuclear pores participates in the transport of γ-tubulin into the nucleus. This finding was confirmed by heterokaryon assay and time-lapse imaging of photoconvertible protein Dendra2 tagged to γ-tubulin. Immunoprecipitation from nuclear extracts combined with mass spectrometry revealed an association of γ-tubulin with tumor suppressor protein C53 located at multiple subcellular compartments including nucleoli. The notion of an interaction between γ-tubulin and C53 was corroborated by pull-down and co-immunoprecipitation experiments. Overexpression of γ-tubulin antagonized the inhibitory effect of C53 on DNA damage G(2) /M checkpoint activation. The combined results indicate that aside from its known role in microtubule nucleation, γ-tubulin may also have nuclear-specific function(s).
Keywords: glioblastom; Brain Neoplasms; Microscopy, Immunoelectron; intracelulární signální peptidy a proteiny; Tubulin; Time-Lapse Imaging; kvantitativní polymerázová řetězová reakce; Cell Nucleus; Cell Line, Tumor; Fluorescent Antibody Technique; fluorescenční protilátková technika; nádory mozku; Cell Nucleolus; časosběrné zobrazování; Tumor Suppressor Proteins; Astrocytes; proteiny nervové tkáně; Genes, Tumor Suppressor; Mitosis; Intracellular Signaling Peptides and Proteins; buněčné jádro; Mass Spectrometry; Real-Time Polymerase Chain Reaction; Immunoprecipitation; nádorové supresorové proteiny; Microtubules; proteiny buněčného cyklu; lidé; Humans; imunoelektronová mikroskopie; Glioblastoma; mikrotubuly; imunoprecipitace; Protein Transport; hmotnostní spektrometrie; mitóza; tubulin; nádorové buněčné linie; astrocyty; Cell Cycle Proteins; tumor supresorové geny; transport proteinů; buněčné jadérko; Nerve Tissue Proteins